An analysis of the influencing factors of depression in older adults under the home care model - You, Yanjie; Huang, Lei; Peng, Xiao; Liao, Lulu; Zhang, Fengjian; Feng, Mingjiao; Chen, Yuqin; Chang, Hongwei; Mo, Beirong; Liu, Yilan (Frontiers in Public Health, 2023)
Objectives To explore and analyze the influencing factors of depression in older adults living at home, so as to propose suggestions for improving the quality of older adults living at home. Methods We conducted a cross-sectional study on 498 older adults living at home based on questionnaire survey on the general information, daily living ability, health status, and care perception (including self-care, care for cohabitants, and care for non-cohabitants) of older adults living at home, as well as their willingness to help each other, and analyzed the influencing factors of depression among older adults living at home. Results The results showed a willingness to help older adults, self-care, and total activities of daily living (ADL), health status was an influential factor for depression in older adults (p < 0.05). Conclusion It aims to take targeted measures, such as encouraging older adults at home to actively participate in mutual assistance activities for older adults and care for themselves, so as to prevent and reduce the occurrence of depression in older adults.